The United Nations and The European Union: A Multifaceted, Differentiated Partnership - Ciss, Ousmane (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
This study focuses on international institutions and their impact in world politics. It presents an analysis of the EU-UN cooperation in Security and crisis management. Applying a neoliberal view of institutionalized cooperation between the two international organizations I am trying to understand how they work together. Many years after its creation the United Nations has been leading many interventions in different zones of the world; enhance peace, and foster local development. Facing many difficulties concerning crisis management the United Nations finds another way to make its operations more effective by working with regional agencies that are also very active and important concerning crisis management into their zones. The European Union as an intergovernmental organization is emerging actor in peacekeeping and peace-building and has been an active partner of the United Nations. The partnership has been differentiated and further developed in different zones. This study tries to understand how the EU and UN cooperate. What have been their participations in the field of peacekeeping, peace-building and human rights? Keywords: European Union, United Nations, Peacekeeping, Peacebuilding, Neoliberal Institutionalism, Human Rights.

ÖZ: Bu çalışmanin odak noktasi uluslararasi kurumlar ve onlarin dünya politikasina etkileridir. AB-BM işbirliği icerisinde Guvenlik ve kriz yönetimi ile ilgili analizini sunmaktadir. İki uluslararasi organizasyon arasindaki kurumlasmisis birliğini ve nasil birlikte calistiklarini yenilikçi liberal bir bakis acisi uygulayarak anlamaya çalışıyorum. Kurulusundan yillar sonra Birlesmis Milletler, dunyanin bircok farkli yerindeki barışı saglamak ve yerel gelişimiarttirmak gibi faaliyetlerde önderlik etmistir. Kriz yonetimi gibi bircok farkli sorunla yuzlesen Birlesmis Milletler, kendi bolgelerinde de yerel olarak aktif ve önemli faaliyetlerde bulunan kurumlarla birlikte çalışarak yaptigi faaliyetleri daha efektif kilmistir. Devletler arasi bir organizasyon olan Avrupa Birliği, dunyada barisi saglamada ve baris ortami olusturmada çok büyük rol oynamistir veuzun yillardir Birlesmis Milletlerin aktif bir partneri olmustur. Dunyanin farkli bolgelerinde bu partnerlik farklilasmakda ve daha ileriye tasinmaktadir Bu arastirma AB ve BM nin nasil is birligi icerisinde olsugunu anlamaya calismaktadir. Bu iki organizasyonun barış saglamada, baris ortami olusturmada ve insan haklariyla ilgili calismalarda katılımları neler olmustur? Anahtar kelimeler: Avrupa Birligi, Birleşmiş Milletler, Barış sağlama, Barış ortami oluşturma, yenilikçi liberal kurumlasma, insan haklari.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2020. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: Political Science and International Relations; United Nations--European Union--Partnership--Politics; Security, International; European Union; United Nations; Peacekeeping; Peacebuilding; Neoliberal Institutionalism; Human Rights